THE INFLUENCE OF PROFITABILITY AND STRUCTURE OF OWNERSHIP ON COMPANY VALUE WITH DIVIDEND POLICY AS AN INTERVENING VARIABLE - Iswara, Ulfah Setia; Setyabudi, Teguh Gunawan (Universitas Serang Raya, 2020)
The established entity has the aim to increase the value of the company. the company's stock price can be a reference for valuing a company. This study aims to test and prove empirically the effect of profitability and ownership structure on firm value with dividend policy as an intervening variable. The research data is in the form of annual company report data listed on the Indonesia Stock Exchange from 2011 to 2016. Data analysis was performed using path analysis. The results showed that profitability and dividend policy had a significant positive effect on dividend policy, while the ownership structure had no effect on dividend policy. Profitability and dividend policy variables proved to have a significant effect on firm value, while ownership structure did not affect company value.